Enhancing Competence in Writing Best Practices Through the Utilization of the STAR Technique - Badriah Badriah; Indra Permana (IKIP Siliwangi, 2023)
Writing proficiency is an essential skill imperative for Indonesian language educators, as it underpins their professional development and advancement. This research presents the adaptation of the STAR writing method's structure to facilitate Indonesian language teachers in reflecting on the process and learning outcomes. The present study adopts a descriptive mode of exposition rooted within a qualitative research paradigm. The research population consists of high schools (SMA) and vocational schools (SMK) in Cianjur Regency. The respondents for this study were 15 Indonesian language teachers from 4 high schools and 1 vocational school. These fifteen teachers willingly participated in the Best Practices writing training for two weeks using both synchronous and asynchronous modes. Data were collected through observations during the training, the outcomes of the activities, and interviews. The data obtained were analyzed using content analysis techniques to identify solutions to the reflective-based writing difficulties experienced by Indonesian language teachers. Based on the research, it was found that: 1) The adaptation of the STAR structure and composition facilitates teachers in logically expressing ideas, 2) The combination of face-to-face and online training assists teachers in re-engaging with writing, and 3) The STAR structure aids teachers in completing their writing within the set time given. The research concludes that teachers are capable of writing when provided with guidance, instructions, and time contracts to complete their writing tasks.